Medicial Education Strategy In The Era of Digitalization and Disruption - Maimun Ihsan; Abdul Kadim Masaong (Universitas Negeri Gorontalo, 2023)
Background: This article aims to (1) examine the current condition of education in the digitalization and disruption era and (2) examine medical education strategies in the digitalization and disruption era. Writing scientific papers is based on library research, whose object of study uses library data in the form of books as a data source.Content: Based on the literature review, it was found that: (1) global medical education currently uses the SPICES strategy (student-centered learning, problem-based, integrated, community-based, elective, and systematic), accompanied by nine educational trends; (2) SPICES is a medical education strategy that will produce graduate profiles that refer to World Health Organization (WHO) and World Organization of Family Doctor (WONCA) conference agreements. A doctor must have six-star doctor characteristics, namely: care provider, decision makers, communicators, community leaders, managers as well as creators and innovators; (2) the minimum standard of competence for doctors in Indonesia, constitute of seven areas of graduate competency namely; has noble professionalism, is always aware and develops himself, can communicate effectively, is reliable in managing information, always has a scientific basis in medical science, has clinical skills and can manage health problems well.Conclusion: A special strategy for medical education is required in the era of digitalization and disruption by applying a lifelong education approach. Indonesian medical education uses the SPICES strategy to create six-star doctors and master the seven defined competency areas.